Functional Nicotinic Acetylcholine Receptors That Mediate Ganglionic Transmission in Cardiac Parasympathetic Neurons - Bibevski, Steve (J Neurosci, 2000)
Nicotinic acetylcholine receptors (nAChRs) mediate ganglionic transmission in the peripheral autonomic nervous system in mammals. Functional neuronal nAChRs have been shown to assemble from a combination of α and β subunits, including α3, α5, α7, β2, and β4 in RNA-injected oocytes, but the subunit composition of functional neuronal nAChRs in vivo in mammals remains unknown. We examined the subunit composition of functional nAChRs in the intracardiac parasympathetic ganglion in a physiologically intact system in vivo. We report here that localized perfusion of the canine intracardiac ganglion in situ with an antagonist specific for nAChRs containing an α3/β2 subunit interface (α-conotoxin MII 100–200 nm) resulted in reversible attenuation of the sinus cycle length (SCL) response by ∼70% to electrical stimulation of the preganglionic vagus nerve. Perfusion with antagonist specific for receptors containing an α3/β4 subunit interface (α-conotoxin AuIB 1 μm) resulted in attenuation in SCL responses (∼20%) compared with baseline when applied by itself, but not in animals pretreated with α-conotoxin MII. Perfusion of the ganglion with α-bungarotoxin (1 μm, which blocks α7 receptors) caused a reduction in SCL response by ∼30% compared with baseline when perfused on its own and when added after blockade with MII and AuIB. Perfusion with hexamethonium bromide resulted in complete blockade of ganglionic transmission, confirming total perfusion of the ganglion and the nicotinic nature of ganglionic transmission at this synapse. Immunohistochemistry using monoclonal antibodies against specific nicotinic subunits confirmed the presence of α3, α7, β2, and β4 subunits. We conclude that functional ganglionic transmission in the canine intracardiac ganglion is mediated primarily by receptors containing an α3/β2 subunit interface, with a smaller contribution by receptors containing α7 nAChRs. Despite the presence of β4 subunits in functional channels, a contribution of a distinct α3/β4 receptor population that does not include an α3/β2 subunit interface was less clear.